Ketahanan Keluarga Pasangan Involuntary Childless Perspektif Hukum Keluarga: Studi Kasus di Simalanggang, Sumatera Barat - Rana, Marta Sucia (Al Muhkam: Journal of Islamic Law and Jurisprudence, 2025)
Marriage in Islam is regarded as a sacred bond (mitsaqan ghalidzan) aimed at establishing a harmonious family and preserving lineage. However, not all married couples are granted children despite sustained efforts. This condition is known as involuntary childlessness, referring to couples who are unable to have children due to medical or biological factors, often resulting in psychological, social, and religious pressures. This study aims to analyze the family resilience of involuntarily childless couples in Simalanggang, West Sumatra, through an integrated perspective of Islamic family law, family psychology, and socio-cultural values of Minangkabau society. The research employs a qualitative method with an empirical approach, combining field research and library research. Data were collected through unstructured interviews and observations involving involuntarily childless couples and local community members, and analyzed descriptively and analytically. The findings indicate that although involuntarily childless couples face social stigma, cultural pressure, and external conflicts, they are able to maintain marital harmony through open communication, emotional support, reinforcement of religious values, and mutual respect. Family resilience is not solely determined by the presence of children, but rather by the quality of the spousal relationship encompassing physical, psychological, social, cultural, and spiritual dimensions. This study contributes to the development of Islamic family law discourse and provides a foundation for formulating social and psychological support policies that are more sensitive to the needs of involuntarily childless couples based on religious and local cultural values.